Professor Formador & Professor Discente: uma relação a ser construída com consciência da sincronicidade - Andrade, Regina Bruhns Rossini (2005)
The goal of this research was to comprehend if the process of formation through which a teacher´s teacher and a teaching student is permeated with the dimensions constructed by sincronic consciousness. To collect the data, I used a questionnaire with two open questions. In it, I try to identify, in the teachers from the Education Major, if these dimensions were lived through or not, with the sincronic consciousness, during their formation process. That is the main focus of this research. I try to comprehend the difficulties that teachers encounter during their formation by using Manacorda and Aranha, reaching back to the history of Education. I observe, by a documental research, the experiences of the first teachers of the Teacher´s School in the XIX Century. In my empirical research, I listened to teachers from public and private Teacher Formation Institutes, about their memories of past experiences of their formation processes. The approach used is a qualitative one, and the data was studied and analysed with the concept created by Placco, of Sincronic Consciousness. These teacher reminiscence, related to the process of formation lived and to the relations established with their own teachers, seem to demonstrate that the actions they consider as positive are the ones in which there is a bound between teacher´s teacher and teacher student. The actions considered negative are the ones in which the relations were permeated with actions and reactions not at all interactive, with a distinctness in one dimension, reinforced by the context in which teacher and student are submersed. Believe that this dichotomy may be overcome by creating a place in which a teacher while working may realize the multiplicity of dimensions in his action, not alone, but with other members of the school. This collaborative culture, especially thought with the sincronic consciousness point of view, makes it possible to attribute meaning to the daily conflicts lived in school